Hazardous Air Pollutant Handbook: Measurements, Properties, and Fate in Ambient Air - Spicer, Chester W (CRC Press, 2009)
Hazardous Air Pollutant Handbook: Measurements, Properties, and Fate in Ambient Air provides a comprehensive review of the 188 compounds and compound classes designated as Hazardous Air Pollutants (HAPs) by the Clean Air Act Amendments of 1990, with a specific focus on their potential presence in ambient air.